Situation Report: Czechoslovakia, 26 May 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Safety in Nuclear Plants Outlook for Trade with the West How to Sell More Goods Abroad Charter 77 Declaration on Elections Charter 77 Interview with Onyszkiewicz